Respon Komunitas Kunghuchu di Pekanbaru Pasca Keluarnya Kepres RI No. 6 Tahun 2000 - Khotimah Khotimah (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2013)
In Indonesia, the history and the recognition of the existence of Khunghuchu religion has ups and downs. In 1965 in accordance with the determination of the President 1 pn.ps/1965 or law No. 5 of 1969 concerning the types of recognized religions are Islam, Catholicism, Protestantism, Hinduism, Buddhism and Khunghuchu. However, the contents of the provision differs from the content of the circular issued by the Ministry of Interior no. 477/74054/BA.01.2/4683/95 November 18, 1978. Letter No. 77/2535/POUD Interior Minister, dated July which states that the type of religion in Indonesia consist of Islam, Catholicism, Protestantism, Hinduism, and Buddhism, however Presidential Decree 6 of 2000 abolished the circular. In the course of religious history of Kunghucu in Pekanbaru, when the Chinese community can not let go of the belief Kunghucu, so they rely on religion (religious master) is valid, ie Buddhism. At the time religion Kunghucu start getting legally, they can not easily escape from menstream of religions. This is piety craving for comfort already in Tridharma, in which there is confidence kunghucu, taoist and Buddhist.